Evidence that bone mineral density plays a role in degenerative disc disease: the UK Twin Spine Study. Issue 12 (22nd June 2010) - Livshits, Gregory; Ermakov, Sergey; Popham, Maria; MacGregor, Alex J; Sambrook, Philip N; Spector, Timothy D; Williams, Frances M K
Abstract : Objective: Osteoarthritis (OA) and osteoporosis are often considered to lie at opposite ends of a spectrum of bone phenotypes. Lumbar degenerative disc disease (LDD) may be associated with low back pain (LBP) and is similar in many ways to OA. LDD is reported in small studies to be associated with increased spine bone mineral density (BMD). The present work aimed to confirm this association in a large population sample using MRI and explore the relationship further, in particular to determine whether it is mediated genetically. Methods: A population based sample (N=908, age range 32–74 years) of UK female twins having MRI of the lumbar spine was used in this study. LDD traits and summary measures and their relationship with BMD at the lumbar spine and hip were examined using multivariate multiple regression and maximum likelihood based variance decomposition. Results: There was a significant positive correlation between LDD and BMD at the lumbar spine and hip, which remained significant after adjustment for confounders. Both traits were highly heritable and the associations between them were mediated genetically. Conclusions: A clear, significant and independent association of BMD at hip and lumbar spine with LDD was found which is, in part, genetically mediated. The association with the non-axial site, the hip, is of particular interest and suggests a systemic bone effect. This should encourage the search for pleiotropic genes to help in the understanding of the bone–cartilage relationship. Moreover, genetic variants identified could provide novel therapeutic targets in the management of LBP.